Use of the Kachanov solution of spherical cavity equilibrium for the analysis of ductile fracture pore growth under irradiation creep - Chirkov, O.Yu. (Reports of the National Academy of Sciences of Ukraine, 2022)
The Kachanov solution of the spherical cavity equilibrium is considered in the elastoplastic body to modeling the ductile fracture pore concentration growth in the material subjected to neutron irradiation. The use of the Kachanov solution for the spherical cavity within the ideal elastoplastic body allows one to consider the irradiation creep on the elastic section of the stress-strain diagram of the irradiated material as compared with the Rice- Tracey-Huang equations where the elastic section is neglected. The consideration of this factor affects the results of the analysis of the porous material behavior. With the increase of the irradiation dose, there is an irradiation strengthening, which leads to the reduction of the material plasticity. Therefore, under long-term irradiation, the role of irradiation creep increases within the elastic section of the stress-strain diagram. Based on the relations from the Kachanov solution, the equation has been obtained to describe the increase of the volume pore concentration in the material depending on the strain increments of instantaneous plasticity and radiation creep. The determining equations of irradiation creep have been formulated to analyze the behavior of the irradiated porous material. In these equations, the nonreversible strains involve the strains of instantaneous plasticity, irradiation swelling, irradiation creep, and structural volume strains considering the ductile fracture pore concentration. The modern models of irradiation swelling and creep are used. They consider the damage dose, irradiation temperature, and influence of the stress state, as well as the accumulated irreversible strain, on the processes of swelling and creep of the material.